Enhanced Circulating-Current Control for the Modular Multilevel Matrix Converter Based on Model Predictive Control - Diaz-Diaz, M (Institute of Electrical and Electronics Engineers Inc., 2019)
This article presents a novel circulating current control scheme for the Modular Multilevel Matrix Converter (M3C). The proposed method is based on a Model Predictive Control strategy (MPC), where an optimization problem is defined for minimizing the tracking error of the circulating currents. The output of the control scheme are circulating voltage references that are defined by a suitable linear transform. The effectiveness of this strategy is compared with a traditional scheme by simulation results of a M3C prototype composed of 27 modules. The reported results exhibit an important enhancement in the regulation of arm currents, specially during transient performance. © 2019 EPE Association.